Filosofi Inkarnasi Pazmino terhadap Konsep Guru Pendidikan Kristen - Wariki, Valentino; Supit, Sigijanti; Tanama, Yulia Jayanti; Halawa, Agnes Monica (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: As a Christian education figure, Pazmino refers a lot to the discourse of incarnation in building and defining the concept of teacher. In some of his works, Pazmino uses a philosophical basis to reconstruct the concept of an incarnative teacher. How does Pazmino construct the theme of the incarnation of Christ as a concept of a Christian education teacher? This article will discuss and examine this theme using the philosophical hermeneutic method. Pazmino explicitly uses the Prologue of the Gospel of John as the initial design of his educational concept. He identifies the incarnation of Christ as the biblical basis of his education. The incarnation of Christ is the best prototype of a teacher. The incarnation of Christ is a reference to the divine action that is responsible for human pedagogical efforts. Therefore, every teacher must prioritize education that is eliminated in the incarnation of Christ. Christian Education Teachers should identify themselves transformatively and participate in God's mission.   Abstrak: Sebagai seorang tokoh pendidikan Kristen Pazmino banyak merujuk kepada wacara inkarnasi dalam membangun dan mendefinisikan konsep guru. Pada beberapa karyanya Pazmino menggunakan landasan filsafat untuk merekonstruksi konsep guru yang inkarnatif. Bagaimana Pazmino menyusun tema inkarnasi Kristus sebagai konsep guru pendidikan Kristen? Artikel ini akan membahas dan mengkaji tema ini dengan metode hermeneutik filosofis. Secara eksplisit Pazmino menggunakan Prolog Injil Yohanes sebagai desain awal konsep pendidikannya.  Ia mengidentifikasi inkarnsi Kristus sebagai dasar biblis pendidikannya. Inkarnasi Kristus merupakan prototipe terbaik seorang guru. Inkarnasi Kristus menjadi rujukan terhadap tindakan ilahi yang bertanggung jawab pada upaya pedagogis manusia. Sebab itu setiap guru harus mengedepankan pendidikan yang berakar pada inkarnasi Kristus. Guru Pendidikan Kristen patut mengidentifikasikan dirinya secara transformatif dan partisipasif pada misi Allah